Application of Android System for Anti-Drug Information. (February 2020) - Maiyana, Efmi; Susanti, Mira; Supratman,; Tria, Yuninda; Ramdalel,
Abstract: Drugs caused the rehabilitee and damage the behavior and mind of men. Then, it's also cause the future life of youth come dullness. Other while, the circulation of drug sale has been using the technology information to catch the target of the target of drugs users. There are many young generation use android. So the android can purposed to prevent the drugs consumption in the youth life. The research in to build an anti drugs application on android basic. It's function to held an interactive dialogue and accommodate the youth creativity, then drug education regarding to improve the service and the young generation care in millennial age for drug mobility eradicating.